2016
DOI: 10.1039/c6cp05321a
|View full text |Cite
|
Sign up to set email alerts
|

Molecular origin of photoluminescence of carbon dots: aggregation-induced orange-red emission

Abstract: The molecular origin of the photoluminescence of carbon dots (CDs) is not known. This restricts the design of CDs with desired optical properties. We have synthesized CDs starting from carbohydrates by employing a simple synthesis method. We were able to demonstrate that the CDs are composed of aggregated hydroxymethylfurfural (HMF) derivatives. The optical properties of these CDs are quite unique. These CDs exhibit an excitation-independent PL emission maximum in the orange-red region (λ ∼ 590 nm). These CDs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(138 citation statements)
references
References 38 publications
(64 reference statements)
6
130
2
Order By: Relevance
“…Moreover, the excitation spectra at λ em = 410 and 560 nm ( Figure 3B) are almost identical to those observed in the ACN solution for the same λ em which indicates that the same two fluorophores 2 and 3 are present in both solutions. The reported excitation and emission spectra of a highlyconcentrated ACN solution of furfural exhibit similar peaks to those presented in this work, greatly supporting the presence of furfural-based derivatives in our humins samples [27]. Finally, based on the previous results we attribute the emission peak (λem = 375 nm) in the pentane fraction to the same species responsible for the emission peak at λ em = 330 nm in the ACN solution (fluorophore 1).…”
Section: Wavelength / Nmsupporting
confidence: 89%
“…Moreover, the excitation spectra at λ em = 410 and 560 nm ( Figure 3B) are almost identical to those observed in the ACN solution for the same λ em which indicates that the same two fluorophores 2 and 3 are present in both solutions. The reported excitation and emission spectra of a highlyconcentrated ACN solution of furfural exhibit similar peaks to those presented in this work, greatly supporting the presence of furfural-based derivatives in our humins samples [27]. Finally, based on the previous results we attribute the emission peak (λem = 375 nm) in the pentane fraction to the same species responsible for the emission peak at λ em = 330 nm in the ACN solution (fluorophore 1).…”
Section: Wavelength / Nmsupporting
confidence: 89%
“…The work by Mandal et al has also recently sought to provide some insights into nanoparticle formation and PL mechanism for sugar-derived CDs [47]. The team studied the reaction between sucrose and H 3 PO 4 to afford excitation-independent orange-red emissive CDs (Ex = 365 nm), which were readily soluble in organic solvents such as DCM and MeCN (Scheme 18).…”
Section: Reviewmentioning
confidence: 99%
“…In a number of brilliant studies, it was shown that, in C-dots formed by thermal treatment of citric acid + amine, the aromatic fluorophores and their associates are observed well before the carbonization occurs [18,[88][89][90][91]. Moreover, the fluorescent C-dots may totally consist of organic dyes [92][93][94]. As we seen below, these facts may suggest the principle of formation of ordered H-aggregated structures.…”
Section: Going Deeper Into Nanocarbon Structures and Their Formationmentioning
confidence: 80%